Formation of Orthogonal Input Value Components in Micro-Processor Current Protection of Distribution Network Lines - F. A. Romaniuk; O. A. Huryanchyk (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper considers formers of orthogonal components with even number read-out and also investigates their frequency and dynamic properties.